INTERAKSI SOSIAL DITINJAU DARI INTENSITAS BERMAIN GAME ONLIE PADA REMAJA - Raden Muhammad Okfiyandi; Desy Arisandy (Jurnal Ilmiah Psyche, 2022)
This study aims to determine the relationship between the intensity of the use of online games with social interaction in adolescents in South Lahat District. The hypothesis proposed in this study is that there is a relationship between the use of online games and social interaction among adolescents in South Lahat District. The number of samples in this study were 105 adolescents in South Lahat District using a sampling technique, namely Simple Random Sampling. The measuring instrument used in this research is the Intensity scale, and the Social Interaction scale. The analysis technique uses a simple regression analysis technique with the help of SPSS version 20. The results of the study using multiple linear regression show a correlation coefficient (r) of 0.762 and an Adjusted R Squeare value of 0.581 = 58.1% with a p value of 0.000 which means there is a very strong relationship. There is a significant relationship between the intensity of online game use and social interaction among adolescents in South Lahat District